Determination of influential factors on edmed surface properties using plackett-burman design - Ndaliman, Mohammed Baba; Khan, Ahsan Ali; Mohammad , Yeakub Ali; Wahid, Zaharah (2012)

(untitled)
In many investigations, large number of process, or design parameters that are initially thought to affect the outcomes or outputs may not really have statistical significant influence on them. Screening experiments are used to identify the key parameters (factors) that significantly affect these outcomes. In this investigation, Plackett-Burman screening design was used to identify the factors that influence the surface properties of titanium alloy (Ti-6Al-4V) during electro-discharge machining (EDM) with Cu-TaC electrodes. These properties are the surface roughness and the surface micro-hardness. The experimental design has seven factors where each factor is set at two different levels. These factors include the TaC composition in the electrode and its compacting pressure. Others are urea concentration in the dielectric fluid, machining peak current, pulse duration, duty factor and the gap voltage. An 8-trial runs was used in conducting the investigation. The analysis of variance was used to analyze the results. The analysis has shown that all the factors except the urea concentration have statistical significant impact on the surface roughness of the EDMed material. On the other hand, the TaC composition and the gap voltage found to have no influence on the surface micro-hardness. The result would lead the way for further round of experimentation for in depth investigation of the factors and their interactions effects.